Molecular genetic medicine. - Friedmann, Theodore, 1935- (Academic Press, 1994)
Continuing to keep pace with progress in human molecular genetics, Volume 4 of Molecular Genetic Medicine reviews five new areas of critical importance. Chapter 1 reviews the molecular mechanisms that have beenunraveled in the pathogenesis of eye diseases. The second chapter explains the remarkable new principle if genomic imprinting, or epigenetic modification imposed by parental history. Chapter 3 describes the etiology of amyotrophic lateral sclerosis, or Lou Gehrig's Disease, as effected by superdioxide dismutase function and neuron degeneration. The fourth chapter covers the normal and aberrant functions of peroxisomes, now implicated in many diseases, most notably adrenoleukodystrophy, publicized widelyby the"cure"called Lorenzo's oil. The final chapter summarizes recombination techniques that permit functional new genetic material to be introduced into, and subsequently transmitted through, the germ line of mammalian cells. These amazing methods arehaving profound impacts on medicine and on concepts of the study of normal human development and disease.